Brain SPECT and MRI Findings in a Uremic Patient With Parkinsonism. (September 2015) - Choi, Eun Kyoung; Oh, Jin Kyoung; Chung, Yong-An; Song, In-Uk
Abstract : Abstract: Parkinsonism associated with basal ganglia pathology represents a rare complication in uremia patients, characterized by acute hyperkinetic or hypokinetic extrapyramidal movement disorders. We herein present brain SPECT and MR findings of uremic patients with end-stage renal failure exhibiting parkinsonian symptoms. The bilateral basal ganglia exhibited decreased uptake on SPECT, and abnormal signals on MR, suggesting pathology.